Simulating the formation of massive protostars - I, Radioactive feedback and accretion disks - Klassen, Mikhail; Pudritz, Ralph E.; Kuiper, Rolf; Peters, Thomas; Banerjee, Robi (The astrophysical journal, 2016)
We present radiation hydrodynamic simulations of collapsing protostellar cores with initial masses of 30, 100, and 200 M ⊙. We follow their gravitational collapse and the formation of a massive protostar and protostellar accretion disk. We employ a new hybrid radiative feedback method blending raytracing techniques with flux-limited diffusion for a more accurate treatment of the temperature and radiative force. In each case, the disk that forms becomes Toomre-unstable and develops spiral arms. This occurs between 0.35 and 0.55 freefall times and is accompanied by an increase in the accretion rate by a factor of 2-10. Although the disk becomes unstable, no other stars are formed. In the case of our 100 and 200 M ⊙ simulations, the star becomes highly super-Eddington and begins to drive bipolar outflow cavities that expand outwards. These radiatively driven bubbles appear stable, and appear to be channeling gas back onto the protostellar accretion disk. Accretion proceeds strongly through the disk. After 81.4 kyr of evolution, our 30 M ⊙ simulation shows a star with a mass of 5.48 M ⊙ and a disk of mass 3.3 M ⊙, while our 100 M ⊙ simulation forms a 28.8 M ⊙ mass star with a 15.8 M ⊙ disk over the course of 41.6 kyr, and our 200 M ⊙ simulation forms a 43.7 M ⊙ star with an 18 M ⊙ disk in 21.9 kyr. In the absence of magnetic fields or other forms of feedback, the masses of the stars in our simulation do not appear to be limited by their own luminosities.
Gesehen am 13.05.2020